A concern visualization approach for improving MATLAB and octave program comprehension - Lessa, I. M.; Carneiro, G.; P. Monteiro, Miguel; Monteiro, M. P.; Brito e Abreu, F. (2015 29th Brazilian Symposium on Software Engineering, 2015)
The literature has pointed out the need for focusing efforts to better support comprehension of MATLAB and Octave programs. Despite being largely used in the industry and academia in the engineering domain, programs and routines written in those languages still require efforts to propose approaches and tools for its understanding. Considering the use of crosscutting concerns (CCCs) to support the comprehension of object-oriented programs, there is room of its use in the context of MATLAB and Octave programs. The literature has purpose and examples in this direction. Considering this scenario, we propose the use of visualization enriched with CCCs representation to support the comprehension of such programs. This paper discusses the use of a multiple view interactive environment called OctMiner in the context of two case studies to characterize how collected information relating to crosscutting concerns can foster the comprehension of MATLAB and GNU/Octave programs. As a result of the conducted case studies, we propose strategies based on OctMiner and tailored to support different comprehension activities of programs written in MATLAB and Octave.